Dynamic modeling and simulation of 4X4 wheeled vehicle. (August 2019) - Chen, Yijie; Zhang, Yafeng; Du, Fu; Wang, Le; Wan, Yiqiang
Abstract: In view of the requirements of military vehicles for high-mobility off-road performance, the dynamic modeling of 4X4 wheeled armored vehicles was carried out. The dynamic model expression expressed in matrix form was derived, and the decoupling calculation was performed by Fourier transform. After that, the power spectral density function was used to characterize the random road input of the vehicle, and the coherence of each wheel excitation in the four-wheeled vehicle was analyzed to derive the coherence coefficient. Finally, the calculation method of vibration response of vehicles under typical roads was formed by programming analysis and reasonable algorithm, and it provided theoretical support for suspension vibration isolation performance design.